Poczucie osamotnienia a wsparcie społeczne i zadowolenie z życia u mężczyzn uzależnionych od alkoholu - Chodkiewicz, Jan; Światkowska, Magdalena (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
The aim of the study was the answer to the a question about social and psychological correlates of feeling of loneliness among males beginning of therapy. The determinants of the feeling of loneliness were identified too. Social and demographical data, social support and life satisfaction were included to independent variables. Research was conducted on 60 alcohol dependent males which are at the beginning of the therapy. Recluse people which undertook therapy in past have the higher level of oneliness. Males with higher level of loneliness are less satisfied with many aspects of their lives and have weaker social support. The results indicated that four of examined variables became the feeling of loneliness predictors: emotional support, social integration, satisfaction with oneself and state of health.